Population policy in Slovenia: From the passive observation to the active mitigation towards sustainable population development - Malačič, Janez (Anali PAZU HD, 2022)
The population policy (PP) of Slovenia and its transition from the second Yugoslavia to the European Union (EU) is analysed in the paper. Recent demographic developments in Slovenia and EU have brought numerous population policy challenges. Therefore, EU has prepared different green papers tackling PP issues. Migration, population ageing and its consequences, adequate pensions as well as the return to the demographic growth and sustainable generation replacement have been more important issues covered. The EU PP developments have been hardly noticed in Slovenia. Consequently, PP paradigm change is necessary in Slovenia. The country needs a shift from passive adaptation to intensive demographic changes to active mitigation of long-term sustainable population development
Keywords: population policy; Slovenia; European Union; sustainable population development